Endoscopic methods in the management of hepatic hydatid disease complications - Uğur YILMAZ,; Burhan ŞAHİN,; Sedat BOYACIOĞLU,; Ülkü SARITAŞ,; Çağlar BAYSAL,; Musa AKOĞLU, (Turkish Journal of Gastroenterology, 2020)
-